URGENSI PENYUSUNAN REGULASI TEKNOLOGI FINANSIAL (IUS CONSTITUENDUM) SEBAGAI INSTRUMEN PERLINDUNGAN HUKUM BAGI KONSUMEN - Muhammad Rafi Mubarak Rafi (Legalita, 2026)
This study aims to analyze the urgency of regulating financial technology (Ius constituendum) in providing legal protection for consumers, including legal safeguards when consumers suffer losses while using financial technology services that are not yet governed by specific regulations. This research is a type of normative legal research, also known as theoretical legal research, as it does not examine the direct implementation or enforcement of the law. Normative legal research is library-based and relies on secondary data as its primary source. The objective of this study is to identify and reveal the urgency of enacting a law on Financial Technology to provide legal protection for consumers in the current digital era. The results indicate that establishing specific fintech regulations (Ius constituendum) is crucial for providing comprehensive legal protection for consumers. The rapid development of fintech services has created new forms of transactions that are not yet fully regulated, resulting in legal gaps and uncertainty. Currently, legal protection for consumers still refers to general provisions, such as the Consumer Protection Law, banking regulations, and the support of Bank Indonesia Regulations (PBI) and OJK Regulations (POJK) as lex specialis in regulating the technical and operational aspects of fintech. This study recommends that the government and legislators promptly formulate specific fintech regulations to accommodate the development of financial technology and ensure legal protection for consumers, including licensing, supervision, data privacy protection, and dispute resolution mechanisms. Clear delineation of authority among supervisory institutions is also necessary to prevent regulatory overlap.